The Realization of Cohesion to Achieve Coherence in the Recount Texts Featured in Grade VIII English Textbooks (Universitas Negeri Semarang, 2021)
A textbook is a crucial part of English language teach since it provides a whole package of materials as well as the activities and assignments. One of the main language materials presented by the textbook is reading texts. These reading texts consist of a lot of genres, one of which is recount text. As a model text used by the teachers and students, it needs to be stylistically well-written and effectively organized. In order to achieve these features, the cohesion and coherence are essential. This study examines the realization of cohesion to achieve coherence in two English textbooks for grade VIII of junior high school students. In conducting this study, qualitative approach with discourse analysis, specifically text analysis, was adopted. Eight recount texts presented in the two textbooks are analyzed using cohesion concept by Halliday and Hasan (2014) and coherence concept by Thornbury (2005). There are three main findings of this study. First, in terms of grammatical cohesion, reference and conjunction dominated the findings; whilst lexical cohesion findings are dominated by collocation. Second, the texts are mostly organized by using the reiteration pattern. Third, the texts share more similarities than differences in regard with the result of the cohesion and coherence analysis. At last, the similarities and differences provide two effects to the text; indicating the texture of the text and representing the text quality. Keywords: textbook, recount text, cohesion, coherence.